Orphan Drug Pricing and Cost Trends in USA: An Analysis of Impact of Orphan Drug ACT - Mishra, Sangita; Madhugiri Prakash, Venkatesh (Indian Journal of Pharmaceutical Education and Research, 2023)
Objectives: The study analyses the impact of incentives in Orphan Drug Act on Orphan Drug revenue strategies of pharmaceutical and biotechnology companies in USA and proposes policies and steps to address the same. Results: There are 389 orphan drugs in circulation as of 2019 with average price of $32,000; prices ranging between $6,000 till more than $500,000. 39% of the marketed drugs costing more than $100,000 treats 23% of patient population. Out of 1.8 million treated patients in 2019, only 0.1% of patients received treatment with drugs having cost greater than $500,000. Orphan drug research and development spending by pharmaceutical and biotechnology companies was 11% of total expenditure of the companies in 2019. The high cost of orphan drugs remains an issue as overall 10% of impacted patient population receiving treatment. Conclusion: The Orphan Drug Act of 1983 has introduced various incentives for pharmaceutical companies to invest more in orphan drug research. It has been observed that there is increase in investment as well as orphan drug approvals because of the incentives and grants. Orphan Drug development is not aligning with the provided incentives and overall cost overall remains high, and availability of treatment is not as expected due to the high costs. Incentives to manufacturers needs to be balanced with treatment availability based on affordable pricing to ensure increased research and higher therapeutic coverage.
Keywords: Orphan Drug Act; Orphan drug; Rare Disease; Volume Based Contract; Outcome Based Contract; Value Based Pricing